2016
DOI: 10.2215/cjn.09830915
|View full text |Cite
|
Sign up to set email alerts
|

Apoprotein B/Apoprotein A-1 Ratio and Mortality among Prevalent Dialysis Patients

Abstract: Background and objectives In dialysis patients, the associations between apoprotein profile and all-cause or cardiovascular disease (CVD)-related mortality are not well known. We, therefore, investigated whether apoprotein levels are associated with these events.Design, setting, participants, & measurements We undertook a prospective observational cohort study of prevalent hemodialysis patients aged $18 years (n=1081), who were followed for 4 years (2011)(2012)(2013)(2014). Outcomes were all-cause and CVD-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 22 publications
4
37
0
2
Order By: Relevance
“…The cause of death was reported by the attending physicians. Definitions of stroke, acute MI, congestive heart failure, and sudden death have also been reported in detail in our previous report .…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The cause of death was reported by the attending physicians. Definitions of stroke, acute MI, congestive heart failure, and sudden death have also been reported in detail in our previous report .…”
Section: Methodsmentioning
confidence: 92%
“…Methods of collecting clinical data, events, and deaths have been detailed in our previous report . Briefly, clinical data were collected from questionnaires recorded by attending physicians.…”
Section: Methodsmentioning
confidence: 99%
“…ApoA-I was significantly associated with all-cause mortality and cardiovascular mortality in HD patients [26] and PD patients [25]. In CKD patients, Cerezo et al revealed that high ApoA-I concentrations have been significantly associated with the development of new cardiovascular episodes and were negatively associated with mortality (but with a lower level of significance) [21].…”
Section: Study Datamentioning
confidence: 99%
“…ApoB is a marker of dyslipidemia and is important in the binding of LDL particles to LDLR (receptor of LDL) for cellular absorption and degradation of LDL par-ticles [11]. Apolipoprotein B (ApoB) is the primary protein component of very low-density lipoproteins (VLDL), intermediate-density lipoprotein (IDL), and LDL-C [11,25,26] and reflects the atherogenic particles from the body [11,25,26]. Other roles of ApoB are displayed in Figure 4 [36].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…A relação entre ApoB/ApoA1 é importante para o adequado transporte lipídico (Barter e Kastelein, 2006), dado que ApoA1 está presente em partículas potencialmente antiaterogênicas e ApoB em partículas aterogênicas. Sato et al (2016) avaliaram a correlação entre ApoA1, ApoB e potencial aterogênico e antiaterogênico e observaram que Apo A-1 foi significativamente correlacionado com HDL (r = 0,86) e apo B foi significativamente correlacionada com LDL, colesterol não HDL e a relação LDL / HDL (r = 0,86, 0,93 e 0,64, respectivamente) evidenciando a necessidade da manutenção das relações adequadas entre ApoB e ApoA1. O valor numérico da relação ApoB/ApoA1 varia de acordo com a espécie (Tabela 3).…”
unclassified